THE EFFECT OF DISCOVERY LEARNING MODEL ON STUDENTS' LEARNING OUTCOMES IN SOCIAL STUDIES FOR GRADE VIII AT SMP PRIVATE TAMANSISWA PEMATANGSIANTAR IN ACADEMIC YEAR 2025/2026 - Ando Julkifli Panjaitan; Tumpal Manahara Siahaan; Herlina Hotmadinar Sianipar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research was motivated by the low learning outcomes of students in social studies, where students tended to be passive and the learning process lacked variation. The objective of this study was to determine the effect of the Discovery Learning teaching model on students' learning outcomes. This study is a quantitative research with a quasi-experimental method. The research sample consisted of two classes: class VIII-B as the experimental group, which was taught using the Discovery Learning model, and class VIII-C as the control group, which was taught using conventional methods. Data were collected through test instruments in the form of pre-test and post-test questions for both classes. The results showed a significant difference in student learning outcomes between the experimental and control groups. Based on the hypothesis test (t-test), the t-count value of 5.12 was greater than the t-table value of 1.67 (at a 0.05 significance level). Thus, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. This proves that there is a significant effect of implementing the Discovery Learning teaching model on students' learning outcomes.